Pelanggaran Hukum Internasional dalam Konflik Yaman Tahun 2015-2019 dan Akibatnya terhadap Situasi Krisis Kemanusiaan - Febriani Amalina Shalihah; Hasan Sidik (Jurnal ICMES, 2021)
This paper aims to review the violations of international laws regarding war crimes and crimes against humanity in the Yemeni conflict 2015-2019 and their consequences for the humanitarian crisis. The review is carried out by referring to non-international armed conflict and using the concepts of International Humanitarian Law, the Rome Statute, and International Human Rights Law. The research method is a qualitative research method using primary data sources from interviews and secondary data from literature studies through books, journals, and related official websites. The results show that many war crimes and crimes against humanity are committed by parties involved in the conflict, such as attacks on civilians and blockade of humanitarian aid supplies to Yemeni territory. These incidents constitute a violation of international law and create a humanitarian crisis in Yemen.